1, 2‐Diketones as photoinitiators of both cationic and free‐radical photopolymerization under UV (392 nm) or Blue (455 nm) LEDs. Issue 6 (10th January 2020) - Zhang, Jing; Wang, Shuhui; Lalevée, Jacques; Morlet‐Savary, Fabrice; Lam, Elizabeth S.‐H.; Graff, Bernadette; Liu, Jing; Xing, Feiyue; Xiao, Pu
ABSTRACT: The photoinitiation abilities of three 1, 2‐diketones [i.e., acenaphthenequinone (ANPQ ), aceanthrenequinone (AATQ ), and 9, 10‐phenanthrenequinone (PANQ )]‐based photoinitiating systems [PISs, with additives such as iodonium salt, N ‐vinylcarbazole (NVK), tertiary amine, and phenacyl bromide (R‐Br)] for cationic photopolymerization and free‐radical photopolymerization under the irradiation of ultraviolet (UV; 392 nm) or blue (455 nm) light‐emitting diode (LED) bulb are investigated. All 1, 2‐diketones studied exhibit ground state absorption that match with the emission spectra of UV (392 nm) or blue LED (455 nm) better than that of the well‐known blue‐light‐sensitive photoinitiator camphorquinone (CQ). In particular, AATQ /iodonium salt/NVK can show high photoinitiating ability (with epoxide conversion yield >70%) under the UV light irradiation due to the effect of NVK. In addition, 1, 2‐diketone/iodonium salt (and optional NVK) systems are capable of initiating free‐radical photopolymerization of methacrylates, with conversions of 50–58%. Furthermore, some 1, 2‐diketone/tertiary amine (and optional R‐Br) combinations are found to demonstrate high efficiency to initiate free‐radical photopolymerization, and 71% of methacrylate conversion can be achieved with PANQ /tertiary amine/R‐Br PIS. Some 1, 2‐ketone‐based PISs can even exhibit higher efficiency than the CQ‐based systems. The photochemical mechanism of the radical generation from the 1, 2‐diketone‐based PISs is investigated and found to be consistent with the related photopolymerization efficiency. © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 792–802 Abstract : Three 1, 2‐diketones (i.e., acenaphthenequinone, aceanthrenequinone, and 9, 10‐phenanthrenequinone)‐based photoinitiating systems (PISs, with additives such as iodonium salt, N ‐vinylcarbazole, tertiary amine, and phenacyl bromide) exhibit the ability to initiate both the free‐radical and the cationic photopolymerization under the ultraviolet or blue light‐emitting diode. Most of the investigated 1, 2‐diketones‐based PISs are even more efficient than the well‐known camphorquinone‐based systems.